Adaptive Algorithms for Solving Eigenvalue Problems in the Variable Computer Environment of Supercomputers - Khimich, O. M.; Popov, O. V.; Chistyakov, O. V.; Kokhanovskyi, V. O. (Cybernetics and systems analysis, 2023)
The authors propose software for the analysis and solution to the algebraic eigenvalue problem using an MIMD computer with GPUs, which includes parallel algorithms and programs with the functions of automatic adaptive configuration of the variable computer environment (multilevel parallelism, variable topology of interprocessor communications, mixed word length, caching, etc.) on the mathematical properties of the problem identified in the computer and the architectural features to ensure the reliability of the solution results and the efficient use of computing resources.